2010
DOI: 10.1088/0004-637x/711/2/1306
|View full text |Cite
|
Sign up to set email alerts
|

The Orbital Period of Swift J1626.6–5156

Abstract: We present the discovery of the orbital period of Swift J1626.6−5156. Since its discovery in 2005, the source has been monitored with Rossi X-Ray Timing Explorer, especially during the early stage of the outburst and into the X-ray modulating episode. Using a data span of ∼700 days, we obtain the orbital period of the system as 132.9 days. We find that the orbit is close to a circular shape with an eccentricity 0.08, that is one of the smallest among Be/X-ray binary systems. Moreover, we find that the timescal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…(2007); 16 Staubert et al. (2011); 17 Raichur & Paul (2010b); 18 in’t Zand, Corbet & Marshall (2001); 19 Kelley, Rappaport & Ayasli (1983); 20 Baykal et al. (2010); 21 Scott et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2007); 16 Staubert et al. (2011); 17 Raichur & Paul (2010b); 18 in’t Zand, Corbet & Marshall (2001); 19 Kelley, Rappaport & Ayasli (1983); 20 Baykal et al. (2010); 21 Scott et al.…”
Section: Discussionmentioning
confidence: 99%
“…If the parameter is known to better than 3 decimal places, it is truncated and the error is smaller than 0.001. References for quantities presented in the Table are given here for each individual system: 1 Kaspi et al (1994); 2 Harmanec et al (2000); 3 Barsukova et al (2005); 10 Finger, Wilson & Hagedon (1994); 11 Hutchings et al (1985); 12 Kaaret, Cusumano & Sacco (2000); 13 Wilson et al (1997); 14 Wang, Johnston & Manchester (2004); 15 Coe et al (2007); 16 Staubert et al (2011); 17 Raichur & Paul (2010b); 18 in't Zand, Corbet & Marshall (2001); 19 Kelley, Rappaport & Ayasli (1983); 20 Baykal et al (2010); 21 Scott et al (1997), Shaw et al (2009);22 Finger et al (1999); 23 Galloway, Wang & Morgan (2005); 24 Wilson et al (2003); 25 Galloway, Morgan & Levine (2004); 26 Wilson, Finger & Camero-Arranz (2008); 27 Baykal et al (2007); 28 Raichur & Paul (2010a); 29 Grundstrom et al (2007); 30 Levine (1991), van der Meer et al (2007); 31 Kreykenbohm et al (2008);…”
Section: Comparison With the Galactic Populationmentioning
confidence: 99%
“…The fluctuation on the residuals is consistent with Doppler delays due to orbital motion. In general for an eccentric orbit, it can be represented as (Deeter et al 1981)(see also in't Zand et al 2001;Baykal et al 2000Baykal et al , 2010, for applications)…”
Section: Timing Analysismentioning
confidence: 99%
“…A Lomb-Scargle periodogram (Lomb 1976;Scargle 1982) of the light curve first revealed an oscillation period from ∼JD 2454000-JD 2454350 September-2007 of ∼47 days and from ∼JD 2454350-2454790 (2007September-2008 of ∼3/2 of this, or ∼72.5 days (DeCesar et al 2009). Recent work by Baykal et al 2010 found the long-term variability timescale to range from ∼45 to 95 days. Additionally, from pulse timing analysis, they find the binary orbit to be nearly circular (eccentricity 0.08) with a period of 132.9 days, meaning the oscillations occur on timescales of ∼1/2 and ∼2/3 of the orbital period.…”
Section: Introductionmentioning
confidence: 99%